Cutaneous manifestation of thyroid carcinoma in a 64-year-old Filipino woman: a case report - Linata, Andrean; Carpio, Benedicto dL; Regalado-Morales, Eileen (Journal of General - Procedural Dermatology and Venereology Indonesia, 2022)
Background: Cutaneous metastasis is a rare phenomenon of thyroid carcinoma. Several mechanisms regarding cutaneous metastasis from internal malignancies have been proposed. Various treatment options are available, including surgical procedures, radioiodine therapy, thyroid hormone therapy, and other possible therapies. The prognosis of thyroid carcinoma with cutaneous manifestation is poor.Case Illustration: We presented a case of 64-year-old female patient with previously diagnosed thyroid carcinoma admitted with enlarged and tender nodules on the right side of the anterior neck. No surgical intervention was done and patient was treated with chemotherapy using doxorubicin 80 mg as the agent of choice. Levothyroxine 100 mcg was also administered every 24 hours. Chemotherapy was given, however the patient eventually died due to respiratory failure.Discussion: The patient initially presented with a slow-growing neck mass, which rapidly developed into larger mass with multiple erythematous to violaceous papules, firm tender nodules, and patches on the thoracic area, indicating slow and rapid progression of the disease. According to histopathologic examination, the patient had papillary thyroid carcinoma. However, the patient poorly responded to the chemotherapy regimen with doxorubicin, which indicated that this malignancy is associated with poor prognosis.Conclusion: Cutaneous metastasis is a rare complication of thyroid carcinoma. Typically, it initially develops as a slow-growing tumor that subsequently progresses into multiple malignant lesions. It is an indicator of poor prognosis in thyroid carcinoma, and further studies are warranted to improve the prognosis of this disease